Mill's Principle of Utility: Origins, Proof, and Implications : Revised and Enlarged Edition - Alican, Necip Fikri (Leiden ; Boston : Brill, 2022)
Mill's Principle of Utility: Origins, Proof, and Implications is a defense of John Stuart Mill's utilitarianism with a particular emphasis on his proof of the principle of utility. Supplemented by a comprehensive historical background as well as salient philosophical assumptions and implications, its primary contribution is an analysis, interpretation, and defense of the controversial proof, which has yet to attract a scholarly consensus on how it works and whether it succeeds. The overarching aim of the book is the vindication of Mill's reasoning in the proof and the restoration of his reputation as one of the clearest thinkers of his time.
Preliminary Material / Necip Fikri Alican -- Copyright Page / Necip Fikri Alican -- Dedication / Necip Fikri Alican -- Foreword / Michael H. Mitias -- Preface / Necip Fikri Alican -- Acknowledgments / Necip Fikri Alican -- A Note on References / Necip Fikri Alican -- Introduction / Necip Fikri Alican -- Chapter 1 Classical Utilitarianism before John Stuart Mill / Necip Fikri Alican -- Chapter 2 The Nature and Function of Mill's Principle of Utility / Necip Fikri Alican -- Chapter 3 The Historical Reception of Mill's Proof of the Principle of Utility / Necip Fikri Alican -- Chapter 4 The Alleged Fallacy of Equivocation in Mill's Proof / Necip Fikri Alican -- Chapter 5 The Alleged Fallacy of Composition in Mill's Proof / Necip Fikri Alican -- Chapter 6 The Alleged Naturalistic Fallacy in Mill's Proof / Necip Fikri Alican -- Chapter 7 Reconstruction of Mill's Proof of the Principle of Utility / Necip Fikri Alican -- Chapter 8 Implications of Mill's Proof of the Principle of Utility / Necip Fikri Alican -- Works Cited / Necip Fikri Alican -- Index / Necip Fikri Alican.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Mill, John Stuart, -- 1806-1873.; Mill, John Stuart, -- 1806-1873.; Mill, John Stuart, -- 1806-1873; Utilitarianism (Mill, John Stuart); Philosophy and religion; Philosophy, Medieval; Philosophy; Philosophy, English -- 19th century; Utilitarianism; Philosophie médiévale.; Philosophie; Philosophie anglaise -- 19e siècle.; Utilitarisme; philosophy; utilitarianism; Philosophy; Philosophy and religion; Philosophy, English; Philosophy, Medieval; Utilitarianism; 1800-1899